2019
DOI: 10.3390/su11236630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pedestrians’ Safety on Urban Intersections: A Visibility Analysis

Abstract: Overall visibility plays a key role in the safety of pedestrians. Despite its importance, verifying the right provisioning of sufficient available sight distances among pedestrians and vulnerable road users (VRUs) is not a prevalent practice. On top of that, the pursuit for more sustainable modes of transportation has promoted the establishment of different shared mobility services which are prone to increase walking and, thus, the number of pedestrians and other VRUs in urban settings. With the intention of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Inadequate visibility of pedestrian is equally associated with increased risk of pedestrian related crashes [21,22]. Poor visibility of pedestrians arises from pedestrians sharing road space with fastmoving vehicles, using motor vehicles that are not equipped with lights, inadequate or lack of roadway lighting [23,24] and pedestrians not wearing reflective accessories or brightly colored clothes [25], especially at night where the risk is greater [26].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate visibility of pedestrian is equally associated with increased risk of pedestrian related crashes [21,22]. Poor visibility of pedestrians arises from pedestrians sharing road space with fastmoving vehicles, using motor vehicles that are not equipped with lights, inadequate or lack of roadway lighting [23,24] and pedestrians not wearing reflective accessories or brightly colored clothes [25], especially at night where the risk is greater [26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more studies have focused on VRUs, including e-bike riders. For instance, Keila González-Gómez’s study identified poor visibility and insufficient sight distance as factors contributing to traffic accidents involving VRUs, while Dasanayaka et al identified driver error and VRU error as key factors in vehicle-VRU collisions and reduced visibility and slower reaction time as key factors contributing to collisions [ 16 , 17 ]. Scarano et al analyzed the cyclist safety research of nearly 10 years by bibliometric methods and found that e-bike and behavior are the main keywords, which showed that people pay special attention to e-bikes and riding behaviors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, goal 11 (to make cities and human settlements inclusive, safe, resilient and sustainable) recognizes the right of people with disabilities to enjoy full social participation [ 10 ] without being discriminated against, with mobility as a fundamental factor in such participation [ 11 ]. Ensuring safety and providing information on urban routes [ 12 ] contribute to achieving these goals. Despite the extensive work that has been carried out, there are still significant gaps between the constructive design of urban environments and the needs of people with disabilities [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%